Studi Penerapan Intelligent Transportation System(ITS) Di Kabupaten Seram Bagian Barat - Hanok Mandaku; Marcus Tukan (ARIKA, 2010)
Transportation is a business transfer of cargo from point of origin to the point of destination with a conveyance or modes. In practice, transportation rarely use only one mode. The goal is to improve the effectiveness and efficiency of transport services. Because it involves more than one mode, then the exchange of information between the modes become very crucial point which is generally a weak implementation of a reliable transport and highly capable. West Seram regency (SBB) today has become "the gate" of Ceram island. In order to spur development of the region, then the function must be set up with good transportation. Therefore, the Intelligent Transportation System (ITS) as one of implementation of Information and Communication Technology (ICT) in the transport sector, should be formed or in the format became the standard, to support the implementation of development activities. Results from this study indicate that the priority of the application of ITS in SBB more focused on economic aspects. From here then prepared road map policy of application of ITS